(Clinical and radiographic results of interlocking nail in fracture reduction of 67 cases small animals) - Leite, Marcella Dall Agnol [UNESP]; Mota, Francisco Cláudio Dantas; Alves, Aracelle Elisane; Mantovani, Matheus Matioli; da Veiga Teixeira, Matheus Franco (Universidade Federal do Paraná, 2021)
Fractures in dogs are one of the great causes of care in small animal surgical clinic. The Interlocking Nail (IN) is a widely used implant, they resist flexion, torsion and axial compression forces. The present study aims to evaluate the time of consolidation, formation of bone callus, and possible complications with the use of IN to reduce fractures. 67 cases were selected in which IN were used to reduce fractures of dogs, which were evaluated clinically e radiographically regarding the time and type of consolidation, early deambulation, complications and limb function. The data obtained was presented in the form of descriptive statistics. It was possible to conclude that IN is an intramedullary implant that allows early return to function as it supports the load placed in the bone during walking, thus allowing the micromovement of the fracture focus, leading to secundary consolidation.
Resultados Clínicos E Radiográficos Da Redução De Fraturas Por Haste Bloqueada Em 67 Cães
Keywords: canine; intramedullary; osteosynthesis